The Role of Technology in Enhancing Digital Literacy Skills Among Secondary School Students - Aoumeur Soufghalem (International Journal of Post Axial: Futuristic Teaching and Learning, 2024)
This study investigates the role of technology in enhancing digital literacy skills among secondary school students. As digital literacy becomes increasingly vital in the modern educational landscape, integrating technology into the curriculum is seen as a key strategy for improving students' competencies in navigating, evaluating, and creating digital content. This research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews to assess the impact of various technological tools and practices on students' digital literacy. The findings indicate that technology plays a significant role in developing digital literacy skills, including information literacy, digital communication, and online collaboration. Students who engaged with interactive digital tools and participated in technology-driven learning activities demonstrated notable improvements in their ability to critically analyze digital information and effectively use digital platforms. However, challenges such as varying levels of access to technology and discrepancies in digital skills among students were also identified.